English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

d = gcd(a,b) ; a = da' and b = db', show that gcd (a', b') =1

2007-01-30 04:58:37 · 3 answers · asked by VT 1 in Science & Mathematics Mathematics

3 answers

If gcd(a',b') = e (<>1)

Then a' = ea'' and b' = eb''
Then a = dea'' and b = deb'' and
de>d so d would NOT be the gcd, unless e = 1.

2007-01-30 05:08:28 · answer #1 · answered by catarthur 6 · 0 0

Suppose a = 30 = 2*3*5, and
b = 42 = 2* 3* 7
Then d = gcd(30,42) = 3
a' = a/d =30/3 = 10, and
b' = b/d = 42/3 = 14
So gcd(a',b') = gcd(10,14) = 2
This is a counter example of your hypothesis, showing that it is not true.

2007-01-30 14:25:12 · answer #2 · answered by ironduke8159 7 · 0 0

by contradiction:
Assume 1 is not gcd(a',b')
let a' =a/d and b' = b/d
let p not equal to 1 be the gcd(a',b')
then a'=pa'' and b'=pb''
substitute:
a=dpa'' and b=dpb''
therefore dp= gcd(a,b) does not equal d.
So, d is and isn't the gcd(a,b)
therefore, by contradiction gcd(a',b')=1

2007-01-30 13:19:20 · answer #3 · answered by onewingedangel37 1 · 0 0

fedest.com, questions and answers